Development of an inhaled anti-TSLP therapy for asthma. (February 2023) - O'Byrne, Paul M.; Panettieri, Reynold A.; Taube, Christian; Brindicci, Caterina; Fleming, Margaret; Altman, Pablo
Abstract: Thymic stromal lymphopoietin (TSLP), an epithelial cell-derived cytokine, acts as a key mediator in airway inflammation and modulates the function of multiple cell types, including dendritic cells and group 2 innate lymphoid cells. TSLP plays a role in asthma pathogenesis as an upstream cytokine, and data suggest that TSLP blockade with the anti-TSLP monoclonal antibody, tezepelumab, could be efficacious in a broad asthma population. Currently approved asthma biologic therapies target allergic or eosinophilic disease and require phenotyping; therefore, an unmet need exists for a therapy that can address Type 2 (T2)-high and T2-low inflammation in asthma. All currently approved biologic treatments are delivered intravenously or subcutaneously; an inhaled therapy route that allows direct targeting of the lung with reduced systemic impact may offer advantages. Currently in development, ecleralimab (CSJ117) represents the first inhaled anti-TSLP antibody fragment that binds soluble TSLP and prevents TSLP receptor activation, thereby inhibiting further inflammatory signalling cascades. This anti-TSLP antibody fragment is being developed for patients with severe uncontrolled asthma despite standard of care inhaled therapy. A Phase IIa proof of concept study, using allergen bronchoprovocation as a model for asthma exacerbations, found that ecleralimab was well-tolerated and reduced allergen-induced bronchoconstriction in adult patients with mild asthma. These results suggest ecleralimab may be a promising, new therapeutic class for asthma treatment.